Dévaluation interne, politiques structurelles et réductions des déficits publics : les réponses apportées par la « troïka » sont-elles un remède aux déséquilibres externes des pays périphériques de la zone euro ? - Francisco Serranito (Revue de la Régulation)
This paper aims at reviewing recent papers on the effects of economic policies advocated by the Troika on peripheral euro zone members. Troika advocates fiscal austerity and internal devaluation policies in the short term and structural policies of market liberalization in the long run. These policies can be considered as a new form of structural adjustment programs. We show that the implementation of these structural adjustment programs in the euro area peripheral countries comes from an erroneous interpretation of the origins of the crisis of sovereign debt. These structural adjustment programs have, however, led to a rebalancing in these countries. The internal devaluation has allowed a reduction in their unit costs of labor and thus improves their price competitiveness. However, we show that this decrease results mainly from cyclical factors; hence it is not sustainable. We suggest, therefore, that adjustment of intra-European imbalances can only be achieved if economic policies are modified in both the core and in the periphery of the euro zone.